Comparison of four tools to identify painful new osteoporotic vertebral fractures in the postmenopausal population in Beijing - Guo, SiJia; An, Ning; Lin, JiSheng; Fan, ZiHan; Meng, Hai; Yang, Yong; Fei, Qi (Frontiers in Endocrinology, 2022)
Abstract Objectives: To compare the validation of four tools including Fracture Risk Assessment Tool (FRAX) without BMD, Beijing Friendship Hospital Osteoporosis Screening Tool (BFH-OST), Osteoporosis Self-Assessment Tool for Asians (OSTA), and bone mineral density (BMD) for identifying painful new osteoporotic vertebral fractures (PNOVFs). Methods: 2874 Postmenopausal women from June 2013 to June 2022 were apportioned into two groups: patients with PNOVFs underwent percutaneous vertebroplasty (PNOVFs group, n = 644), and community-enrolled females (control group, n = 2230). Magnetic resonance imaging and X-rays were used to confirm PNOVFs. Dual-energy X-ray absorptiometry was used to calculate BMD T-scores. Osteoporosis was diagnosed according to WHO criteria. Data on clinical and demographic risk factors were self-reported using a questionnaire. The ability to identify PNOVFs by FRAX, BFH-OST, OSTA, and BMD scores was evaluated using receiver-operating characteristic (ROC) curves. Areas under the ROC curves (AUCs), sensitivity, specificity, and optimal cutoff points were identified. Results: There were significant differences in FRAX (without BMD) scores, BFH-OST scores, OSTA scores, and BMD T-scores (total hip, femoral neck, and lumbar spine) between the PNOVFs group and control group. Compared to BFH-OST, OSTA, and BMD, the FRAX score had the best identifying value for PNOVFs: the AUC of the FRAX score (optimal cutoff =3.6%) was 0.825, and the sensitivity and specificity were 82.92% and 67.09% respectively. Conclusion: FRAX may be a preferable tool for identifying PNOVFs in postmenopausal populations. BFH-OST and OSTA might be applied as a simple screening tool for PNOVFs.